Elementary particles : building blocks of matter - Fritzsch, Harald, 1943-2022 (Hackensack, NJ : World Scientific, 2005)
This highly readable book uncovers the mysteries of the physics ofelementary particles for a broad audience. From the familiar notionsof atoms and molecules to the complex ideas of the grand unificationof all the basic forces, this book allows the interested lay public toappreciate the fascinating building blocks of matter that make up ouruniverse.
Introduction. -- Electrons and atomic nuclei. -- Quantum properties of atoms and particles. -- The knives of Democritus. -- Quarks inside atomic nuclei. -- Quantum electrodynamics. -- Quantum chromodynamics. -- Mesons, baryons, and quarks. -- Electroweak interactions. -- Grand unification. -- Conclusion.
Includes index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Particles (Nuclear physics) -- Popular works; Quantum chromodynamics -- Popular works; Quantum electrodynamics -- Popular works; Particules (Physique nucléaire) -- Ouvrages de vulgarisation; Chromodynamique quantique -- Ouvrages de vulgarisation; Électrodynamique quantique -- Ouvrages de vulgarisation; SCIENCE -- Physics -- Nuclear; SCIENCE -- Physics -- Atomic & Molecular; Particles (Nuclear physics); Quantum chromodynamics; Quantum electrodynamics; Popular works